2013
DOI: 10.1111/dote.12015
|View full text |Cite
|
Sign up to set email alerts
|

Predictive biomarkers for Barrett's esophagus: so near and yet so far

Abstract: SUMMARY Barrett’s esophagus (BE) is the strongest risk factor for the development of esophageal adenocarcinoma. However, the risk of cancer progression is difficult to ascertain in individuals, as a significant number of patients with BE do not necessarily progress to esophageal adenocarcinoma. There are several issues with the current strategy of using dysplasia as a marker of disease progression. It is subject to sampling error during biopsy acquisition and interobserver variability among gastrointestinal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 52 publications
0
27
0
1
Order By: Relevance
“…Phases 3 and 4 entails validation in retrospective and prospective studies, respectively. This is followed by Phase 5 studies that evaluate the impact of a biomarker on the population disease burden and primary outcomes such as costs and mortality rates [24]. Although many biomarkers have been identified and evaluated in Phase 3 and few in Phase 4 studies, none have progressed through and validated in a Phase 5 trial.…”
Section: Biomarkers In Risk Stratification For Barrett's Esophagusmentioning
confidence: 99%
“…Phases 3 and 4 entails validation in retrospective and prospective studies, respectively. This is followed by Phase 5 studies that evaluate the impact of a biomarker on the population disease burden and primary outcomes such as costs and mortality rates [24]. Although many biomarkers have been identified and evaluated in Phase 3 and few in Phase 4 studies, none have progressed through and validated in a Phase 5 trial.…”
Section: Biomarkers In Risk Stratification For Barrett's Esophagusmentioning
confidence: 99%
“…38 An important epigenetic change is the methylation of CpG nucleotides found in promoter genes which can regulate gene expression and silencing. 38,39 Both hypermethylation and hypomethylation can contribute to cancer development based on involvement of suppression gene or oncogene. Studies have identified differences in methylation patterns of normal esophageal mucosa and BE / EAC.…”
Section: Epigenetics: Dna Methylation and Micrornamentioning
confidence: 99%
“…6,46 While P53 can be used in combination with dysplasia to predict increased risk of cancer, it has limited role in risk stratification of non-dysplastic BE. 38 IHC of p53 along with histopathology exam is likely more practical than genotyping for LOH of p53 which can potentially identify all mutations in the p53 gene. Recent British society of gastroenterology (BSG) BE guidelines recommends consideration of p53 immunostaining as an adjunct to routine histopathologic diagnosis of dysplasia in the risk stratification of BE subjects.…”
Section: Protein Markersmentioning
confidence: 99%
See 2 more Smart Citations